Kemampuan Pasing Bawah Bola Voli Pada Siswa Kelas V Di Sekolah Dasar Negeri Tanjungrejo Kecamatan Buluspesantren Kabupaten Kebumen Tahun Ajaran 2024/2025: Penelitian - Puput Widodo; Akhmad Sulaiman Tri Wandono (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
One of the requirements to be able to play volleyball well is that players must be equipped with good basic techniques. Underhand Passing is a basic technique or movement in volleyball. The purpose of this study was to determine the Underhand Passing Ability of Volleyball in Grade V Students of Tanjungrejo Elementary School, Buluspesantren District, Kebumen Regency. This study is a quantitative descriptive study, which means that this study describes the facts and characteristics of the object or topic being studied in an accurate and methodical manner. The sample used in this study were all grade V students of Tanjungrejo Elementary School, consisting of 22 students, consisting of 8 boys and 14 girls. The variable studied was the underhand passing ability of grade V students of Tanjungrejo Elementary School. The instrument used was the Brady Wall Volleyball Test which had been modified and developed to measure the underhand passing movement ability. Data analysis in this study was carried out using a quantitative descriptive method, with a percentage. The results of this study are the skills of passing under Volleyball in SDN Tanjungrejo, Buluspesantren District, Kebumen Regency are categorized as very lacking by 0.00% (0 students), lacking by 45.45% (10 students), sufficient by 31.82% (7 students), good by 9.09% (2 students), very good by 13.64% (3 students). So it can be concluded that the skills of passing under volleyball of grade V students of SDN Tanjungrejo are categorized as lacking.